E-commerce : real issues and cases - Knapp, Michael C. 4 0 16; 5 (Australia ;;Mason, Ohio : Thomson/South-Western, 2003)
A guide to e-commerce that includes case studies of failed dot-com companies, discussion of the various issues surrounding e-commerce, and a listing of related reading.
Includes bibliographical references (p. 86-87) and index.
Reference and Research Book News
Adult;Adult
Keywords: 2 -- 0; 6; Electronic commerce; 20; 2